The Influence of Sustainability Factors on Greenhouse Gas Emissions Disclosure through Governance Roles in Indonesia's Energy Sector - Yana, Via Sukma; Astuti, Christina Dwi (Universitas Medan Area, 2025)
On account of the issue of climate change and the increasing demand for environmental transparency, the disclosure of greenhouse gas (GHG) emissions is being encouraged by firms. With governance as a moderating variable, the purpose of the present study is to explore the effect of ESG (Environment, Social, Governance) funds, sustainable development goals, and sustainable strategic management on GHG emission disclosure. In the study, stakeholder theory and legitimacy theory were used to analyze how business tries to gain trust of stakeholders by meeting their expectations and offering transparent information. This study is based on a sample of 131 companies taken from the annual reports and sustainability reports in the energy sector companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023. The results indicate that GHG emission disclosure is linked to sustainable strategic management and ESG investments. In fact, beyond a new moderating governor variable not being apportioned in the previous Wahyuningrum et al.'s [34] study,iplinary implementation etc. (2024), this research is original, as it employs such independent variables as sustainable development goals, sustainable strategic management, and ESG funds. Based on the findings of this study, energy sector firms could enhance GHG emissions disclosure to be more transparent in communicating with its stakeholders by increasing the distribution of ESG fund and the integration of sustainability strategy.